Estudo do uso de tecnologias em pesquisas que tratam da educação financeira - Castelo Branco, Anísio Costa (2018)
This paper presents the mapping of thirty dissertations and theses dealing with the theme of Financial Education in the context of Teaching and Mathematics Education in the period between 2014 and 2016 in order to identify if and how technology is considered in such works. Initially, the definition of mapping, its objectives and the paths taken to its accomplishment are discussed. The objective is to analyze the contributions of the technologies in graduate academic productions about Financial Education, in the context of Mathematics Education, through a meta-synthesis, in order to identify how this topic is being discussed in the researches and the role of technology in these studies. They point to several solutions and we have identified suggestions and taken notes of the difficulties and the need to use technologies to improve the teaching of Financial Education